Penanggulangan Tindak Pidana Pencurian dengan Kekerasan (Curas) di Wilayah Hukum Kepolisian Resor Kota Besar Palembang - Okta Rianda; Ruben Achmad; Hambali Yusuf (Jurnal Hukum Lex Generalis, 2024)
The incidence of robbery with violence (curas) in Indonesia remains high and fluctuating. Prevention in the Palembang Police jurisdiction combines penal and non-penal measures. Penal efforts include legal actions and deterrence through investigation and prosecution, resulting in sentences such as 1 year and 8 months of imprisonment. Non-penal strategies focus on prevention via public education, patrols, community empowerment, economic improvement, and social development. Influencing factors include legal ambiguities, limited law enforcement resources, inadequate infrastructure, low public legal awareness, fear of retaliation, lack of trust in the police, and cultural tolerance for curas. Comprehensive measures are essential for sustainable prevention.